Influence of Agronomic Practices on Growth and Yield of Chickpea (Cicer arietinum L.) - Khemendra Choudhary; Amarjeet; Parveen Kumar; Rohtas Kumar; Chander Shekhar; Rajendra Singh Beniwal; Pradeep Kumar (Archives of Current Research International, 2025)
Weed management is a critical aspect of chickpea (Cicer arietinum L.) cultivation, influencing its growth and yield potential. As one of the leading pulse crops cultivated globally, chickpea faces significant challenges from weed competition, which can severely hinder crop development by competing for vital resources such as light, water, and nutrients. The study investigated the impact of various crop establishment methods and weed management practices on the growth and yield of chickpea (Cicer arietinum L.) over two consecutive rabi seasons (2022–23 and 2023–24) at the regional research station, Bawal, CCS Haryana Agricultural University, Hisar. The experiment was laid out using a split-plot design, consisting of 30 treatment combinations comprising six crop establishment methods, viz. E1- Normal row spacing under zero tillage (45-45 cm), E2- Paired row spacing under zero tillage (30:60 cm), E3- Normal row spacing under conventional tillage, E4- Paired row spacing under conventional tillage, E5- Normal row spacing under bed planting and E6- Paired row spacing under bed planting in main plot and five weed management treatments are W1- Pendimethalin 30% EC (1000 g/ha at pre-emergence), W2- Pendimethalin 30% EC (1000 g/ha at pre-emergence) + one hand weeding at 25-30 DAS, W3- Two hand weeing at 25-30 and 45-50 DAS, W4- Weedy check and W5- Weed free in subplot. Each treatment combination was replicated three times. Results indicated that bed planting with normal row spacing significantly improved leaf area index (LAI) and seed yield, achieving maximum LAI values of 1.649 and 1.714 and seed yields of 1675.8 and 1760.7 kg ha⁻¹ in 2022-23 and 2023-24, respectively. Among weed management treatments, weed-free plots and those managed by two hand weeding (25-30 and 45-50 DAS) consistently outperformed others, reflecting significantly higher LAI and grain yields.